Exploring Causes of Frustration for Software Developers - Ford Robinson, Denae; Parnin, Chris (In proceedings of the IEEE ICSE 9th International Workshop on Cooperative and Human Aspects of Software Engineering (CHASE), 2015)
When learning to program, frustrating experiences contribute to negative learning outcomes and poor retention in the field. Defining a common framework that explains why these experiences occur can lead to better interventions and learning mechanisms. To begin constructing such a framework, we asked 45 software developers about the severity of their frustration and to recall their most recent frustrating programming experience. As a result, 67% considered their frustration to be severe. Further, we distilled the reported experiences into 11 categories, which include issues with mapping behaviors to code and broken programming tools. Finally, we discuss future directions for defining our framework and designing future interventions.